5qSMA: standardised retrospective natural history assessment in 268 patients with four copies of SMN2 - Vill, Katharina; Kamm, Christoph; Mensch, Alexander; Weiler, Markus; Ziegler, Andreas (Journal of neurology, 2024)
Newborn screening for 5qSMA offers the potential for early, ideally pre-symptomatic, therapeutic intervention. However, limited data exist on the outcomes of individuals with 4 copies of SMN2, and there is no consensus within the SMA treatment community regarding early treatment initiation in this subgroup. To provide evidence-based insights into disease progression, we performed a retrospective analysis of 268 patients with 4 copies of SMN2 from the SMArtCARE registry in Germany, Austria and Switzerland. Inclusion criteria required comprehensive baseline data and diagnosis outside of newborn screening. Only data prior to initiation of disease-modifying treatment were included. The median age at disease onset was 3.0 years, with a mean of 6.4 years. Significantly, 55% of patients experienced symptoms before the age of 36 months. 3% never learned to sit unaided, a further 13% never gained the ability to walk independently and 33% of ambulatory patients lost this ability during the course of the disease. 43% developed scoliosis, 6.3% required non-invasive ventilation and 1.1% required tube feeding. In conclusion, our study, in line with previous observations, highlights the substantial phenotypic heterogeneity in SMA. Importantly, this study provides novel insights: the median age of disease onset in patients with 4 SMN2 copies typically occurs before school age, and in half of the patients even before the age of three years. These findings support a proactive approach, particularly early treatment initiation, in this subset of SMA patients diagnosed pre-symptomatically. However, it is important to recognize that the register will not include asymptomatic individuals.